Newsround. (November 2020) - Parikh, Tulsi
Abstract: 'Newsround' offers a platform for new discoveries that do not appear within the specialist contributions of this year's Archaeological Reports, but which nevertheless warrant emphasis, either as a result of their particular characteristics or for the contribution they make to broader archaeological narratives. This section is not intended to be exhaustive but rather an overview of archaeological research in Greece. It comprises largely preliminary reports (results of excavations that took place up to and including August 2020 where possible) that complement the digital content made available through Archaeology in Greece Online (https://chronique.efa.gr ). Due to the diachronic nature of a number of the sites and for ease of reference, the material is organized geographically in the first instance and then chronologically (earliest to latest) within each section as far as possible.